Teachers' beliefs and experiences regarding collaboration across language subjects. - Haukås, Åsta; Drange, Eli-Marie Danbolt (Journal of Multilingual & Multicultural Development, 2026)
In schools worldwide, there are increasing expectations for teacher collaboration across subjects. However, despite the potential benefits for students and teachers of viewing language subjects as interrelated, limited research has explored how meaningful collaboration across different language subjects can be undertaken. Addressing this gap, this study investigates language teachers' experiences with and perspectives on collaboration across language subjects. Data were generated from focus group discussions with teachers of Norwegian, English, French, German, and Spanish in four Norwegian secondary schools and analysed through reflexive thematic analysis. The analysis revealed that teachers had limited prior experience in this area but recognised several potential benefits, such as increased language awareness and a more holistic understanding of languages. However, teachers' suggestions for collaboration mainly focused on sharing ideas and coordinating tasks, whereas deeper forms of joint work are likely necessary to achieve lasting learning effects. Moreover, teachers lacked knowledge of each other's subject curricula, whereas a crucial starting point for effective collaboration would be for teachers to become familiar with the contents of all language subject curricula in school. Finally, the analysis suggests that effective collaboration requires active leadership support to address practical challenges and develop a shared understanding of what collaboration may entail.